STRATEGI GREEN ACCOUNTING SEBAGAI BAGIAN PENERAPAN ETIKA BISNIS PADA UMKM - Sayekti Indah Kusumawardhany (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2022)
The existence of SMEs is expected to boost the country's economy. This is evident from BPS data that SMEs in Indonesia account for 60% of state revenue. The growth of SMEs which continues to increase, seems to leave a negative impact on the surrounding environment. The fact that can be seen is from the disposal of production waste from a business. The application of environmental accounting will encourage the ability to minimize the environmental problems it faces. SMEs can use a green accounting strategy, namely by including environmental costs in the accounting system used. The existence of a green accounting strategy used in SMEs can increase the value of business ethics. This study uses the literature study method as the main source of data collection. In Indonesia, SME owners consciously understand the importance of being responsible for the environment, but SME owners do not understand how to report environmental costs. Most of the SME owners apply green accounting but do not report on the financial statements.